2007
DOI: 10.1063/1.2783961
|View full text |Cite
|
Sign up to set email alerts
|

High performance thin film transistors with cosputtered amorphous indium gallium zinc oxide channel

Abstract: The authors report the fabrication of high performance thin film transistors (TFTs) with an amorphous indium gallium zinc oxide (a-IGZO) channel, which was deposited by cosputtering using a dual IGZO and indium zinc oxide (IZO) target. The effect of the indium content on the device performance of the a-IGZO TFTs was investigated. At a relatively low IZO power of 400W, the field-effect mobility (μFE) and subthreshold gate swing (S) of the a-IGZO TFTs were dramatically improved to 19.3cm2∕Vs and 0.35V/decade, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
200
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(211 citation statements)
references
References 10 publications
5
200
0
1
Order By: Relevance
“…The better interface between the IO semiconductor and the Al 2 O 3 gate insulator also affected the hysteresis. 31 The gate bias stability is an important parameter in the assessment of materials and devices for further integrated applications. Resistances to positive gate bias stressand to negative gate bias stress are highly desirable for display applications.…”
Section: Resultsmentioning
confidence: 99%
“…The better interface between the IO semiconductor and the Al 2 O 3 gate insulator also affected the hysteresis. 31 The gate bias stability is an important parameter in the assessment of materials and devices for further integrated applications. Resistances to positive gate bias stressand to negative gate bias stress are highly desirable for display applications.…”
Section: Resultsmentioning
confidence: 99%
“…1(a-c)). Crucially, they demonstrated that such a device could exhibit high mobility, stimulating much work on this system [24,25]. A second milestone on the road towards oxide electronics can be seen as the observation of the integer [26] and, more recently, fractional [27] quantum Hall effects in ZnO/MgZnO heterostructures by Tsukazaki et al (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous articles, the decrease in the subthreshold swing may be attributed to the interface and bulk trap density of the TFTs [11]. In general, charge trapping is characterized by the total trap density (N t ), including the bulk trap density (N b ) of the channel layer and the interface trap density (N it ) between the dielectric/channel.…”
Section: Resultsmentioning
confidence: 98%